THE EFFECT OF GENRE-BASED APPROACH AND LEARNER AUTONOMY TOWARD THE WRITING COMPETENCE OF THE EIGHTH GRADE STUDENTS OF SMP HARAPAN NUSANTARA - ., NI MADE SRI ARTINI; ., PROF. DR. I KETUT SEKEN, M.A.; ., DR. I GEDE BUDASI, M.Ed.DIP APPLIN (Jurnal Pendidikan Bahasa Inggris Indonesia, 2016)
This study aimed at: a) finding out whether or not there is a significant difference in writing competence between the students who were taught by using genre based approach and those who were taught by using a conventional strategy; b) finding out whether or not there is an effect of the interaction between the implementation of genre based approach and learner autonomy on the students writing competence; 3) finding out whether or not there is a significant difference in writing competence between the students with high autonomy treated by using genre based approach and those treated by using a conventional strategy; 4) finding out whether or not there is a significant difference in writing competence between the students with how autonomy who are treated by using genre based approach and those treated by using a conventional strategy. The study employed a post test for control group and an experiment group with 2 x 2 factorial designs. The population of the study was 196 eighth grade students of SMP Harapan Nusantara in academic year 2015/2016 where in 144 of them were selected as the sample of the study through cluster random sampling technique. The data were collected by means of attitude questionnaire and writing competence test and were analyzed by using Two-Way ANOVA and Tukey test. The result of this research such as: a) there was significant difference in writing competence between the students who are taught by using genre based approach and those who are taught by using a conventional strategy, b) there was significant effect of the interaction between the implementation of genre based approach and learner autonomy on the students’ writing competence, c) there was significant difference in writing competence between the students with high autonomy treated by using genre based approach and those treated by using a conventional strategy and d) there was significant difference in writing competence between the students with low autonomy who are treated by using genre based approach and those treated by using a conventional strategy. Kata Kunci : Genre-Based Approach, Learner Autonomy, Writing Competence Penelitian ini bertujuan untuk : a) mengetahui perbedaan dalam prestasi anatara siswa yang diajarkan dengan pendekatan genre dan cara konvensional; b) mengetahui efek interaksi anatara mode pembelajaran dan sikap siswa dala prestasi menulis, c) mengetahui perbedaan prestasi siswa yang diajarkan dengan pendekatan genre dan cara konvensional pada siswa yang memiliki kemandirian belajar yang tinggi, d) mengetahui perbedaan prestasi siswa dengan kemandirian belajar yang rendah diajatkan dengan pendekatan genre dan konvensional. Penelitian ini menggunakan Post Test Only control group dengan desain 2x2 faktorial. Populasi penelitian ini adalah siswa kelas delapan tahun ajaran 2013/2014 dengan jumlah 196 dimana 144 siswa dipilih sebagai sampel dengan menggunakan metode Cluster Random Sampling. Data dikumpulkan menggunakan instrument berupa kuesioner untuk mengetahui sikap siswa terhadap pembelajaran menulis dan berupa kuesioner untuk mengetahui sikap siswa terhadap pembelajaran menulis dan berupa tes tulis untuk mengetahui kempuan siswa dalam menulis paragraf naratif kemudian data dianalisa menggunakan Two-Way ANOVA dan Tukey Test. Hasil dari test tersebut yaitu : a) adanya sebuah perbedaan dalam prestasi anatara siswa yang diajarkan dengan pendekatan genre dan cara konvensional; b) adanya sebuah efek interaksi anatara mode pembelajaran dan sikap siswa dala prestasi menulis, c) adanya sebuah perbedaan prestasi siswa yang diajarkan dengan pendekatan genre dan cara konvensional pada siswa yang memiliki kemandirian belajar yang tinggi, d) adanya sebuah perbedaan prestasi siswa dengan kemandirian belajar yang rendah diajatkan dengan pendekatan genre dan konvensional. keyword : Pendekatan Genre, Kemandirian Siswa, Kompetensi Menulis.